Pemecahan Masalah Matematika melalui Metode Defragmenting - Suci Haryanti (JKPM (Jurnal Kajian Pendidikan Matematika), 2018)
The purpose of the study is to findways to solve mathematical problems to make it easier and fun and also able to remember the concept in the long run with the defragmenter method is to reconstruct the mindset to be easier when used or recalled in solving math problems Tthe method used in this study is literature study by using theoretical study approach. From the study there are three components that obtained : 1) scanning, 2) check some errors, 3) Repairing, 4)give a chance to re-work 5) certain the results.